ANALYSIS OF THE CAUSE AND IMPROVEMENT OF VARIABLES IN MEDICAL LABORATORIES - Anood Abdurahman Aloumi, Ghidaa Abdullah Fakih, and Buthaynah Abdalrahman Alodhayb (Chelonian Research Foundation, 2024)
Medical laboratories play a crucial role in the healthcare system by providing accurate and timely diagnostic information to healthcare providers. However, several variables can impact the quality and reliability of laboratory results, leading to potential errors in patient care. This essay aims to analyze the causes of variables in medical laboratories and propose improvements to enhance the accuracy and efficiency of laboratory testing. By critically examining the literature, this essay will provide a comprehensive understanding of the challenges faced by medical laboratories and suggest strategies to mitigate these challenges.